VD_FINDINFO Arrêt / 2012 / 387 vom 6. März 2012 - VD Tribunal cantonal (2012)
TUTELLE, CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, PROPORTIONNALITÉ | 369 al. 1 CC, 370 CC, 392 ch. 1 CC, 393 ch. 2 CC, 397 al. 2 CC, 393 CPC